Managing Osteoporosis in Patients on Long‐Term Bisphosphonate Treatment: Report of a Task Force of the American Society for Bone and Mineral Research. (January 2016) - Adler, Robert A; Fuleihan, Ghada El‐Hajj; Bauer, Douglas C; Camacho, Pauline M; Clarke, Bart L; Clines, Gregory A; Compston, Juliet E; Drake, Matthew T; Edwards, Beatrice J; Favus, Murray J; Greenspan, Susan L; McKinney, Ross; et al.
ABSTRACT: Bisphosphonates (BPs) are the most commonly used medications for osteoporosis. This ASBMR report provides guidance on BP therapy duration with a risk‐benefit perspective. Two trials provided evidence for long‐term BP use. In the Fracture Intervention Trial Long‐term Extension (FLEX), postmenopausal women receiving alendronate for 10 years had fewer clinical vertebral fractures than those switched to placebo after 5 years. In the HORIZON extension, women who received 6 annual infusions of zoledronic acid had fewer morphometric vertebral fractures compared with those switched to placebo after 3 years. Low hip T ‐score, between –2 and –2.5 in FLEX and below –2.5 in HORIZON extension, predicted a beneficial response to continued therapy. Hence, the Task Force suggests that after 5 years of oral BP or 3 years of intravenous BP, reassessment of risk should be considered. In women at high risk, for example, older women, those with a low hip T ‐score or high fracture risk score, those with previous major osteoporotic fracture, or who fracture on therapy, continuation of treatment for up to 10 years (oral) or 6 years (intravenous), with periodic evaluation, should be considered. The risk of atypical femoral fracture, but not osteonecrosis of the jaw, clearly increases with BP therapy duration, but such rare events are outweighed by vertebral fracture risk reduction in high‐risk patients. For women not at high fracture risk after 3 to 5 years of BP treatment, a drug holiday of 2 to 3 years can be considered. The suggested approach for long‐term BP use is based on limited evidence, only for vertebral fracture reduction, in mostly white postmenopausal women, and does not replace the need for clinical judgment. It may be applicable to men and patients with glucocorticoid‐induced osteoporosis, with some adaptations. It is unlikely that future trials will provide data for formulating definitive recommendations. © 2015 American Society for Bone and Mineral Research.